A history of the Antisemitic 1934 Montreal Hospital Strike - Groszman, Lilly; Weisz, George (Canadian Medical Education Journal, 2024)
On June 15th, 1934, interns at Montreal’s Notre Dame Hospital initiated Canada’s first medical strike in protest of the appointment of Dr. Samuel Rabinovitch, a French-speaking Jewish graduate of Université de Montréal, as chief intern. By June 16th, the strike had spread to 75 more interns from Hôpital de la Miséricorde, Sainte-Justine, Hôtel-Dieu, and St. Jean-de-Dieu. The strike was purely antisemitic, targeting the first Jewish physician appointed to a staff position at a Catholic hospital. By situating the strike within its social context, Rabinovitch’s story exemplifies medicine’s history of systemic racism and highlights the contradiction between these practices and the medical principle of “do no harm.” Our aim is to provide a comprehensive analysis of the relationship between Montreal’s medical history and antisemitism in the first half of the twentieth century. We conclude that the strike reinforces the historical basis of promoting racial diversity and inclusion in medical education.